PENGARUH SOSIALISASI TERHADAP TINGKAT PENGETAHUAN PERAWAT TENTANG EARLY WARNING SYSTEM (EWS) DI RUANG RAWAT INAP DEWASA RS SIMPANGAN DEPOK - Febby Nursakinah; Lannasari Lannasari; Marisca Agustina (JURNAL ILMIAH NUSANTARA, 2024)
Knowledge and experience are factors that influence a nurse's ability to identify patients whose condition is worsening. Poor knowledge about a patient's critical condition and the signs that appear can slow down the process of identifying patients who are experiencing a worsening condition. Failure by nurses to recognize changes in the patient's clinical condition in the hospital inpatient room can result in unexpected events, namely resulting in unplanned transfer of the patient to the intensive care unit, cardiac arrest and death. The aim of this research is to determine the effect of socialization on nurses' level of knowledge about the Early Warning System (EWS) in the adult inpatient ward at Simpangan Hospital, Depok. The research method that will be used is a pre-experimental research design, one group t test- pre test using the Wilcoxone test. The results of the distribution of characteristics are that the majority of respondents are female (65%), have at least a D3 education (75%), and have worked for ≥ 4 (35%). The results of the distribution of nurses' knowledge before being given the EWS socialization intervention showed that the majority of pre-intervention nurses' knowledge level was sufficient, 12 respondents (60%), less than 5 respondents (25%), and good 3 respondents (15%). The results of the distribution of nurses' knowledge after being given the EWS socialization intervention were good for 9 respondents (45%), sufficient for 7 respondents (35%), and less than 4 respondents (20%). There is an influence of socialization on the level of nurses' knowledge about the Early Warning System (EWS) in the adult inpatient room at Simpangan Depok Hospital with a P value of 0.002 (p<0.05), so it can be concluded that there is a significant difference between the knowledge scores before and after the intervention. EWS socialization. Suggestions for hospitals to provide education and outreach more often regarding NEWS filling, to improve the quality of knowledge and performance.